Prohibition of Drinking Alcohol in Public: A Legal Analysis of Malaysian Law - Rajamanickam, Ramalinggam; Zahir, Mohd Zamre Mohd; Mohamad, Mafuzah; Karunanithi, Kanagaraj; Ganesan, Dhina Dharshan (Journal of Posthumanism, 2025)
The public consumption of alcohol in Malaysia presents multifaceted legal, social, and health challenges, particularly in light of the country’s diverse cultural and religious composition. While alcohol is legally permitted for non-Muslims, Malaysia lacks a comprehensive federal law that specifically prohibits or regulates drinking in public spaces. Existing laws, including the Penal Code, Road Transport Act 1987, Excise Act 1976, and various local government bylaws, address alcohol-related concerns in a fragmented manner, leading to inconsistent enforcement and public confusion. Furthermore, Syariah enactments applicable only to Muslims further complicate the legal landscape, creating disparities in regulation and enforcement based on religious affiliation. This article critically examines the current statutory and regulatory framework governing public alcohol consumption in Malaysia, highlighting significant legislative gaps and enforcement challenges. By adopting a qualitative methodology, it draws on comparative legal models from jurisdictions such as Singapore, India, and the United Kingdom to demonstrate how coherent and targeted legal interventions can promote public order while respecting individual freedoms. Based on this analysis, the article proposes a structured, federal-level legal framework that incorporates uniform definitions, designated alcohol-free zones, time-based restrictions, and standardised local enforcement mechanisms. In advocating for reform, the article underscores the need for legal clarity, institutional coordination, and public education. A well-designed legal infrastructure would enhance regulatory coherence, promote responsible alcohol use, and reinforce public confidence in the rule of law. By balancing legal pluralism with universal principles of public safety and health, Malaysia can address the current legal ambiguities and build a more effective and inclusive regulatory system for managing alcohol consumption in public spaces.